Ophthalmic Microsurgery Lab for Medical Students: Enhancing Learner Intrinsic Motivation and Comfort with Microsurgery - Cole, Joshua; Chen, Tiffany A.; Ahmad, Tessnim; Parikh, Neeti (Journal of Academic Ophthalmology, 2021)
Objective This study aimed to evaluate the impact of an ophthalmic microsurgery laboratory on medical students' intrinsic motivation, explicit interest in ophthalmology, and comfort with microsurgical skills.Design In this noncontrolled trial, medical students attended a Zoom-based lecture on corneal suturing, watched an instructional video on operating microscopes, and attended a wet laboratory on corneal suturing. Participants completed pre- and posttest surveys assessing comfort with microsurgical skills and explicit interest in ophthalmology. Additionally, the posttest survey included items from the Intrinsic Motivation Inventory (IMI).Setting This study was conducted at a single academic medical center.Participants A total of 20 students enrolled in the MD program at the University of California, San Francisco School of Medicine.Results Pre- and posttest response rates were 100% (n = 20) and 90% (n = 18), respectively. Comfort with microsurgical skills increased significantly between pre- and posttest surveys with large effect sizes (95% confidence interval [CI]; p-value): loading a needle, 1.67 (1.04–2.29; p < 0.001); passing a suture, 1.72 (1.04–2.40; p < 0.001); knot tying, 1.05 (0.34–1.76; p = 0.004); using a microscope, 0.83 (0.04–1.63; p = 0.040); and suturing under a microscope, 1.44 (0.88–2.00; p < 0.001). Comparing pre- and posttest surveys, students reporting moderate to extreme interest in ophthalmology increased from 44 to 61%. Intrinsic motivation was high, indicated by the mean IMI Interest score reaching 93% of the maximum score. Multiple linear regression analyses predicted that IMI Interest scores increased with higher scores of familiarity (p = 0.002), explicit interest in ophthalmology (p = 0.042), and comfort with microscopes (p = 0.005), knot tying (p = 0.026), and performing surgical maneuvers under a microscope (p = 0.032).Conclusion Ophthalmic microsurgery laboratories may increase medical students' explicit interest in ophthalmology, comfort with microsurgical skills, and intrinsic motivation. Future studies are needed to evaluate the impact of microsurgical electives on students' objective skills and specialty selection.
Keywords: undergraduate medical education; ophthalmology; microsurgery; motivation; surgical simulation